EFL Students’ Perceptions and Challenges in Using Talk Shows to Improve Listening Skills - Permatasari, Riski; Purwanti, Indah Tri (Lectura : Jurnal Pendidikan, 2025)
In response to the increasing need for authentic, engaging materials in English language teaching, this study explores the potential of talk shows as a medium to enhance listening comprehension. This study aims to investigate students’ perceptions, challenges, and learning experiences in using talk shows as a medium to improve listening skills. In the context of the digital era, media-based learning, such as talk shows, offers valuable opportunities to enhance listening comprehension. As authentic audio-visual materials, talk shows expose learners to natural spoken English, diverse accents, and real-life conversational contexts. This research employed an explanatory sequential mixed-method design, beginning with a quantitative phase involving 74 sixth-semester students, followed by a qualitative phase with seven participants selected to provide deeper insights. Data were collected through a 25-item questionnaire and structured interviews. The findings indicate that students held positive perceptions of talk shows, particularly in five areas: language exposure, listening skill development, motivation and engagement, learning methods and habits, and personal preferences. Nevertheless,some challenges were noted, including difficulties with fast speech, unfamiliar vocabulary, and accent variation. Overall, students viewed the use of talk shows to be both beneficial and meaningful. Future research is encouraged to explore the long-term impact of talk shows or to compare their effectiveness with other language learning media.